HIGH-RESOLUTION RADIOAUTOGRAPHY OF GALACTOSE-(3)H ACCUMULATION IN RINGS OF HAMSTER INTESTINE - Stirling, Charles E. (The Rockefeller University Press, 1967)
Radioautography of water-soluble substances has posed a major technical problem for the past decade. Utilizing silicone-impregnated plastic sections of frozen-dried tissue, a quantitative method was developed for studying distribution of (3)H-labeled galactose, mannitol, and phlorizin. The content of a 2-µ band may be measured with an accuracy of ±20% by light microscopy; radioautographs may also be prepared for the electron microscope. Results with intestinal tissue incubated 1–10 min in vitro and, then, frozen rapidly indicate that the first step in galactose absorption is uphill transport into the brush border of the columnar epithelium. Correction of galactose content for the mannitol space in the brush border suggests that the sugar pump is located at the surface of the microvilli. Further evidence for the surface locus of the glucose-galactose pump was obtained with phlorizin (next paper, reference 40). The galactose content of columnar cell cytoplasm always equalled that of microvilli and no transcellular diffusion gradient could be detected; during the first minutes of incubation, however, a gradient did exist between nucleoplasm and cytoplasm. Downhill exit of galactose from columnar cells may have proceeded either directly across basal membranes to adjacent lamina propria or indirectly via open intercellular spaces. Lastly, even in the absence of muscularis, the connective tissue of the lamina propria constituted enough of a diffusion barrier so that it served as a secondary accumulating compartment for galactose under present in vitro conditions.